Pharmacy industry research: conditioned by market interests? - Páez Moreno, Ricardo (Acta Bioethica, 2011)
Research sponsored by pharmacy industry obeys to scientific interests of highest quality, but at the same time to several economic interests, since being funded by transnational corporations must be subjected to rules imposed by market. This article questions the measure in which this dynamic conditions scientific integrity and the search for treatments for great health needs. Through literature review, it is shown how scientific innovation has diminished and research priorities are conditioned by market.